Education, Innovation and Software Production: The Use of Reflective Practice - Andrade, Aline; Albuquerque, Regina; Dors, Tania Mara; Binder, Fabio Vinicius; Malucelli, Andreia; Reinehr, Sheila (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2021: Anais do XX Simpósio Brasileiro de Qualidade de Software, 2021)
∗great demand for professionals qualified for applications (apps) development. The required profile includes technical skills, also known as hard skills, and behavioral or soft skills. The training of these professionals in speed, quantity, and quality demanded by the market poses a significant challenge for educational institutions. Apple and PUCPR have established a partnership to build a software studio to develop such talents using the Challenge Based Learning (CBL) method and associated practices whose effects need to be studied. This research aims to analyze the contributions of reflective practice in a software studio that aims to teach the main professional competencies regarding app development, including hard and soft skills. The research method used was the case study, based on semistructured interviews with 18 participants carried out in two cycles. The collected data were analyzed with the support of open and axial coding from Grounded Theory and Atlas.ti tool. The results demonstrate that reflective practice, applied in a software studio environment that uses CBL was able to help students to map new ideas and acquire valuable hard and soft skills. The study pointed out that reflective practice is an effective instrument for developing the skills required by the app market, which demands innovation and quality at high speed.